DECIPHERING BIODEGRADATION EFFECTS ON LIGHT HYDROCARBONS IN CRUDE OILS USING THEIR STABLE CARBON ISOTOPIC COMPOSITION: A CASE STUDY FROM THE GULLFAKS OIL FIELD, OFFSHORE NORWAY - Vieth A.; Wilkes H. (My University, 2006)
Compound-specific isotope analysis has become an important tool in environmental studies and is an especially powerful way to evaluate biodegradation of hydrocarbons. Here, carbon isotope ratios of light hydrocarbons were used to characterise in-reservoir biodegradation in the Gullfaks oil field, offshore Norway. Increasing biodegradation, as characterised, for example, by increasing concentration ratios of Pr/ n-C17 and Ph/n-C18, and decreasing concentrations of individual light hydrocarbons were correlated to 13C- enrichment of the light hydrocarbons. The ?13C values of C4 to C9 n-alkanes increase by 7-3? within the six oil samples from the Brent Group of the Gullfaks oil field, slight changes (1-3?) being observed for several branched alkanes and benzene, whereas no change (<1?) in ?13C occurs for cyclohexane, methylcyclohexane, and toluene. Application of the Rayleigh equation demonstrated high to fair correlation of concentration and isotope data of i- and n-pentane, n-hexane, and n-heptane, documenting that biodegradation in reservoirs can be described by the Rayleigh model. Using the appropriate isotope fractionation factor of n-hexane, derived from laboratory experiments, quantification of the loss of this petroleum constituent due to biodegradation is possible. Toluene, which is known to be highly susceptible to biodegradation, is not degraded within the Gullfaks oil field, implying that the local microbial community exhibits rather pronounced substrate specificities. The evaluation of combined molecular and isotopic data expands our understanding of the anaerobic degradation processes within this oil field and provides insight into the degradative capabilities of the microorganisms. Additionally, isotope analysis of unbiodegraded to slightly biodegraded crude oils from several oil fields surrounding Gullfaks illustrates the heterogeneity in isotopic composition of the light hydrocarbons due to source effects. This indicates that both source and also maturity effects have to be well constrained when using compound-specific isotope analysis for the assessment of biodegradation. ? 2005 Elsevier Inc. All rights reserved.
Keywords: BIODEGRADATION; CRUDE OIL; ISOTOPIC COMPOSITION; ATLANTIC OCEAN; GULLFAKS FIELD; NORTH SEA